2017
DOI: 10.1007/s12020-017-1434-y
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin circulating levels and 10-year (2002–2012) cardiovascular disease incidence: the ATTICA Study

Abstract: In our study, elevated circulating total adiponectin levels were associated with lower 10-year CVD risk in adults without previous CVD, independently of other established CVD risk factors. This association appeared to be modestly attenuated by CRP, yet was not mediated by interleukin-6 which is the main endocrine/circulating pro-inflammatory cytokine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 77 publications
0
11
0
1
Order By: Relevance
“…Adiponectin represents a multifaceted biomarker that may beneficially affect atherosclerosis, inflammation and insulin resistance pathways [8]. In humans, it has been indicated that low adiponectin concentrations associated with metabolic syndrome [9], atherosclerosis [10], hypertension [11] and cardiovascular disease [12]. Adiponectin has protective actions in the initiation and progression of atherosclerosis through anti-inflammatory and anti-atherogenic effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin represents a multifaceted biomarker that may beneficially affect atherosclerosis, inflammation and insulin resistance pathways [8]. In humans, it has been indicated that low adiponectin concentrations associated with metabolic syndrome [9], atherosclerosis [10], hypertension [11] and cardiovascular disease [12]. Adiponectin has protective actions in the initiation and progression of atherosclerosis through anti-inflammatory and anti-atherogenic effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…Levels of adiponectin, an adipose-specific protein, are inversely associated with levels of adiposity [39]. Consequently, lower levels of adiponectin are linked to increased risk for obesity, insulin resistance, diabetes, cardiovascular and other diseases [40,41,42]. Increases in plasma adiponectin concentrations have been observed with the obstruction of the renin-angiotensin system [43], increased HDL concentrations, and decreased body mass index [44].…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of adiponectin in 1995 [1], this hormone, mainly secreted by the adipose tissue and initially called adipocyte complement-related protein of 30 kDa (Acrp30), has drawn a great deal of attention due to its possible protective effect against type 2 diabetes, its anti-inflammatory effects and its anti-atherogenic properties [2][3][4][5]. It has also aroused controversy, given that although various studies reported that high plasma adiponectin levels were associated with lower cardiovascular disease risk [6][7][8][9], others were unable to confirm its protective effect against cardiovascular diseases or total mortality [10][11][12].…”
Section: Introductionmentioning
confidence: 99%